Utwór naukowy a komercjalizacja rezultatów twórczych w świetle prawa o szkolnictwie wyższym - Machała, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
It is believed that universities may play proncipal role in the process of innovations. It is crucial to provide adequate legal background to enhance academics to create on the one hand, and to enable universities to put the effects of academics’ creativity on the market – on the other hand. The provision of such legal framework was the main purpose of the recent amendement to Law on Higher Education. However, the adopted rules have left some extent of uncertainty as regards the legal status of works created by academics. This article focuses on the issue of the status of copyrighted scientific works. In principle, such works are not subject to employer’s copyright (regulated by art. 12 and 74 section 3 of Law on Copyright and Neighbouring Rights), the employer (university or other establishment of higher education) is only granted the priority regarding the publication of employee’s work (provided that certain additional conditions are met) – art. 14 of Law on Copyright and Neighbouring Rights. Thus, university’s position vis-a-vis their employees works is somehow weak, and additionally the enforcement of priority granted by virtue of art. 14 is dubious. On the other hand, Law on Higher Education (as amended) provides that university hold rights to effects of its employee’s development works and may commercialise them or transfer rights thereto (art. 86d and following of Law on Higher Education). These effects of develompment works may in some cases be scientific works as well (eg. concept of market use of certain data may constitute an effect of development works and scientific work at the same time). It is trerefore crucial to asses which legal rule applies to objects being scientific works and effects of development works at the same time. It is argued that according to principle lex specialis derogat legi generali art. 86d of Law on Higher Education has priority before art. 14 of Law on Copyright and Neighbouring Rights, although some authors hold the contrary opinion.